2019
DOI: 10.1097/pai.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

PAX8 Expression Variability in Cerebellar Hemangioblastoma: Case Series and Review of the Literature

Abstract: Hemangioblastomas are benign tumors of undetermined origin, and account for up to 2.5% of all intracranial tumors. They may occur either sporadically or as a manifestation of von Hippel-Lindau (VHL) syndrome. Central nervous system (CNS) hemangioblastomas are pathologically diagnosed by gross and microscopic morphology, with further support of the diagnosis conferred by a characteristic immunohistochemistry profile including PAX8 negativity. Although renal hemangioblastomas have previously been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Studies have shown that labeling with inhibin alpha, S-100, and CD10 help to distinguish RH from renal clear cell carcinoma. Inhibin alpha and S-100 are usually positive in RH and negative in renal clear cell carcinoma and contrast; CD10 is usually positive in renal clear cell carcinoma and negative in RH [30][31][32][33]. Our cases are also consistent with the results of the above studies.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that labeling with inhibin alpha, S-100, and CD10 help to distinguish RH from renal clear cell carcinoma. Inhibin alpha and S-100 are usually positive in RH and negative in renal clear cell carcinoma and contrast; CD10 is usually positive in renal clear cell carcinoma and negative in RH [30][31][32][33]. Our cases are also consistent with the results of the above studies.…”
Section: Discussionsupporting
confidence: 90%